Results of the National Cholesterol Education (NCEP) Program Evaluation Project Utilizing Novel E-Technology (NEPTUNE) II Survey and Implications for Treatment Under the Recent NCEP Writing Group Recommendations - Davidson, Michael H.; Maki, Kevin C.; Pearson, Thomas A.; Pasternak, Richard C.; Deedwania, Prakash C.; McKenney, James M.; Fonarow, Gregg C.; Maron, David J.; Ansell, Benjamin J.; Clark, Luther T.; Ballantyne, Christie M. (The American journal of cardiology, 2005)
The most recent national survey of compliance with the National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) guidelines was completed before ATP III and showed significant underachievement of low-density lipoprotein (LDL) cholesterol goals. The NCEP Evaluation ProjecT Utilizing Novel E-Technology (NEPTUNE) II was a national survey conducted in 2003. Of the 4,885 patients, 67% achieved their LDL cholesterol treatment goal, including 89%, 76%, and 57%, respectively, in the 0 or 1 risk factor, ≥2 risk factors or coronary heart disease (CHD), and CHD risk equivalent categories. The percentage with triglyceride concentrations ≥200 mg/dl (2.25 mmol/L) in each risk category who achieved their LDL cholesterol and non-high-density lipoprotein cholesterol goals was 64%, 52%, and 27%, respectively. Patients with diabetes (55%) and other CHD risk equivalents (40%) were less likely to have achieved their LDL cholesterol targets than those with CHD (62%). Of the 1,447 patients with cardiovascular disease, 75% could be classified as very high risk according to the new July 2004 NCEP Writing Group recommendations, and 17.8% of those at very high risk had an LDL cholesterol level of <70 mg/dl (<1.81 mmol/L). In conclusion, these results suggest improved lipid management compared with previous surveys. The largest treatment gaps were found for features new to ATP III as of July 2004, including goal achievement for patients with CHD risk equivalents and for non-high-density lipoprotein cholesterol targets. Most of those (75%) with cardiovascular disease in NEPTUNE II would be considered very high risk and candidates for aggressive therapy to reach the new optional treatment goals.